Resisting Patriarchal Hegemony: Baiduri’s Struggle Against Walid as a Religious Opportunist in the Series Bidaah - Mohammad Maulidina Irawan; Yoga Rifqi Azizan (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study examines the representation of patriarchal hegemony and forms of women’s resistance in the Bidaah series through the perspectives of Antonio Gramsci’s hegemony and Simone de Beauvoir’s existentialist feminism. The main focus of this study is on the power relations established by the character Walid as a religious leader, as well as the resistance efforts undertaken by the character Baiduri in dismantling the practice of exploiting religion. The method used is a descriptive qualitative approach with data analysis techniques in the form of dialogue, gestures, and expressions of characters in relevant scenes. The results of the study indicate that patriarchal hegemony in this series is built through consensus originating from ideology, popular beliefs, and common sense that are legitimized by religious symbols. Walid plays the role of a traditional intellectual who not only produces discourse but also instills values that are voluntarily accepted by the congregation. This hegemony is evident in ritual practices, pondok rules, and social relations that place women as subordinate subjects. On the other hand, Baiduri is presented as a representation of an organic intellectual who carries out resistance through critical awareness, verbal rejection, and symbolic actions against unjust practices. From an existentialist feminist perspective, Baiduri’s resistance reflects an attempt at transcendence, a critique of patriarchal myth, biology, and psychoanalysis, and a struggle for freedom and existential autonomy. Baiduri rejects the labeling of women as passive and affirms her existence as an independent subject. Thus, this study emphasizes that resistance to patriarchal hegemony is not always confrontational, but can emerge through intellectual awareness and the courage to question established authority. The Bidaah series not only represents the practice of religious-based domination but also presents an emancipatory narrative about women’s struggle to maintain their dignity and freedom.